Distinguishing infectivity in patients with pulmonary tuberculosis using deep learning - Gao, Yi; Zhang, Yiwen; Hu, Chengguang; He, Pengyuan; Fu, Jian; Lin, Feng; Liu, Kehui; Fu, Xianxian; Liu, Rui; Sun, Jiarun; Chen, Feng; Yang, Wei; et al. (Frontiers in Public Health, 2023)
Introduction: This study aimed to develop and assess a deep-learning model based on CT images for distinguishing infectivity in patients with pulmonary tuberculosis (PTB).We labelled all 925 patients from 4 centres with weak and strong infectivity based on multiple sputum smears within a month for our deep-learning model named TBINet's training. We compared TBINet's performance in identifying infectious patients to that of the conventional 3D ResNet model. For model explainability, we used gradient-weighted class activation mapping (Grad-CAM) technology to identify the site of lesion activation in the CT images.The TBINet model demonstrated superior performance with an area under the curve (AUC) of 0.819 and 0.753 on the validation and external test sets, respectively, compared to existing deep learning methods. Furthermore, using Grad-CAM, we observed that CT images with higher levels of consolidation, voids, upper lobe involvement, and enlarged lymph nodes were more likely to come from patients with highly infectious forms of PTB.Our study proves the feasibility of using CT images to identify the infectivity of PTB patients based on the deep learning method.